Young people in question(s). Eleven case studies from Africa - (:unkn) unknown (My University, 2020)
How should young people and youth in Africa be conceived of? How can one avoid reducing the great diversity of existences among the majority to the tragic condition experienced by a minority? What are the best means of durably increasing knowledge, beyond conventional wisdow and sensationalist clichés? What can be done with a category based on age, that improbable criterion which originates in the biological evolution of human beings, and serves as a demographic instrument to measure individuals in population censuses, and is used for a wide variety of purposes by politicians and journalists, and is thwarted by the actors themselves in their interactions?Through case studies, many of which were written by authors who are themselves young people, this issue offers a new comparative anthropology of youth. It deconstructs the historicity of the “youth” category and its late arrival in the field of African studies, and reminds us that customs can still have a bearing on young people's development. Reference points are highlighted in the profusion of works, and questions are formulated for new studies. Between the local and global, it presents a framework for comparison with other types of youth throughout the world, as well as the means for supplementing analyses that are overly marked by the single stamp of globalisation.
Keywords: African Research